Determinants of Service Quality in the Hospitality Industry: The Case of Malaysian Hotels - M. Sadiq Sohail; Matthew H. Roy; Mohammad Saeed; Zafar U. Ahmed (Journal of Accounting, Business and Management (JABM), 2007)
Many nations, states, and geographic regions have focused on tourism as a means to economic growth. Most recently, East Asia has experienced a huge influx in tourist dollars as demand grew more than twice as fast as world averages. Tourist often follows the recommendation of others who have had a pleasant experience. The main objective of this study is to examine the factors that influence consumer perceptions of service quality in a mid-priced hotel chain in Malaysia. A random sample of 50 hotel guests provided both survey and interview data regarding the efficacy of different services. The results provide insights and lead to suggestions for change in hotel management practices.